2021
DOI: 10.3390/nu13082876
|View full text |Cite
|
Sign up to set email alerts
|

Is the Activity-Based Anorexia Model a Reliable Method of Presenting Peripheral Clinical Features of Anorexia Nervosa?

Abstract: Anorexia nervosa (AN) causes the highest number of deaths among all psychiatric disorders. Reduction in food intake and hyperactivity/increased anxiety observed in AN are also the core features of the activity-based anorexia animal model (ABA). Our aim was to assess how the acute ABA protocol mimics common AN complications, including gonadal and cardiovascular dysfunctions, depending on gender, age, and initial body weight, to form a comprehensive description of ABA as a reliable research tool. Wheel running, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 51 publications
1
6
1
Order By: Relevance
“…Some studies have shown that excessive exercise causes an increase in ALT levels [42,43], while other scientific reports suggest that regular mild physical activity lowers the ALT level [44,45]. In our study, the statistically significant lower level of ALT in the ABA group could have been caused by additional physical exercise, however, it is not consistent with our previous research on the animal model, which showed that the Expanded insights into the neural component of the activity-based anorexia animal model... liver enzymes were negatively affected by increased physical activity [30]. The ambiguous correlation between physical exercise and ALT levels could be the reason behind the different results in our studies.…”
Section: Discussioncontrasting
confidence: 93%
See 4 more Smart Citations
“…Some studies have shown that excessive exercise causes an increase in ALT levels [42,43], while other scientific reports suggest that regular mild physical activity lowers the ALT level [44,45]. In our study, the statistically significant lower level of ALT in the ABA group could have been caused by additional physical exercise, however, it is not consistent with our previous research on the animal model, which showed that the Expanded insights into the neural component of the activity-based anorexia animal model... liver enzymes were negatively affected by increased physical activity [30]. The ambiguous correlation between physical exercise and ALT levels could be the reason behind the different results in our studies.…”
Section: Discussioncontrasting
confidence: 93%
“…There are a few proposed mechanisms including excessive exercise, depletion of liver glycogen, ineffective gluconeogenesis and issues with glucagon secretion [54]. In our experimental group, the glucose level was significantly lower than in the control group, and severe hypoglycemia was also observed in ABA rats -this is consistent with our previous study on the ABA model [30]. It is well established that hypoglycemia in ABA rodents is caused by food restriction, whereas in exercised controls the glucose level is not significantly altered [55][56][57].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations